The Fiscal Efficiency of Excise Duty on Tobacco Products in Poland under Sustainable Development Conditions - Edyta SYGUT (Communications of International Proceedings, 2021)
Excise duty on tobacco products is a moderately sustainable tax. In 2004-2019, it reduced the tobacco product consumption level in Poland, while maintaining high fiscal efficiency understood as the capacity to collect budget revenue. The taxation of cigarettes was particularly significant for the revenue from excise duty on tobacco products in Poland in 2004-2019. Due to the occurrence of multicollinearity between the average price of a cigarette pack and the legal consumption volume, only one of the specified explanatory variables should be taken into consideration for the model of revenue from excise duty on tobacco products. Based on the example of cigarettes, it was concluded that excise duty rate is a tool which simultaneously supports the implementation of objectives related to sustainable development, and fosters the fiscal efficiency of excise duty on tobacco products.
Keywords: excise duty; tobacco products; fiscal efficiency; sustainable development